Numerical results for the CGBI method to viscous channel flow - Kräutle, Serge; Wielage, Kerstin (The Navier-Stokes Equations: Theory and Numerical Methods, 2001)
The conjugate gradient boundary iteration (CGBI) is a domain decom- position method for elliptic partial differential equations [1] [2] [3] [6 ] [7]. In the context of fractional step methods [10], a Navier-Stokes solver based on CGBI and a characteristic’s method was constructed. In this article, numerical results for the incompressible flow past a backward facing step and past a cylinder (both modelled in 2d) are presented.